Rivals - McGee, Katharine (McGee, Katharine. American royals (Series), 2022)
In an alternate America, Beatrice, now queen, and her sibilings Samatha and Jefferson struggle to untangle their personal lives and settle into their new political roles while the country hosts the world's monarchs at the League of Kings conference.